Development of a 3He nuclear spin flip system on an in-situ SEOP 3He spin filter and demonstration for a neutron reflectometer and magnetic imaging technique. (April 2016) - Hayashida, H; Oku, T; Kira, H; Sakai, K; Hiroi, K; Ino, T; Shinohara, T; Imagawa, T; Ohkawara, M; Ohoyama, K; Kakurai, K; Takeda, M; et al.
Abstract: We have been developing a 3 He neutron spin filter (NSF) using the spin exchange optical pumping (SEOP) technique. The 3 He NSF provides a high-energy polarized neutron beam with large beam size. Moreover the 3 He NSF can work as a π-flipper for a polarized neutron beam by flipping the 3 He nuclear spin using a nuclear magnetic resonance (NMR) technique. For NMR with the in-situ SEOP technique, the polarization of the laser must be reversed simultaneously because a non-reversed laser reduces the polarization of the spin-flipped 3 He. To change the polarity of the laser, a half-wavelength plate was installed. The rotation angle of the half-wavelength plate was optimized, and a polarization of 97% was obtained for the circularly polarized laser. The 3 He polarization reached 70% and was stable over one week. A demonstration of the 3 He nuclear spin flip system was performed at the polarized neutron reflectometer SHARAKU (BL17) and NOBORU (BL10) at J-PARC. Off-specular measurement from a magnetic Fe/Cr thin film and magnetic imaging of a magnetic steel sheet were performed at BL17 and BL10, respectively.